New exploration model and engineering application of urban karst groundwater channel based on the 3D electrical method - Wang, Xiang; Yang, Mingwei; Zhu, Yuan; Liang, Jingwei; Jiang, Huangbin (Frontiers in Earth Science, 2025)
The detection of karst groundwater channels is of great significance for the development of underground cities and the prevention and control of geological disasters. Aiming at the characteristics of high spatial variability of karst geological groundwater channels, a new exploration model based on the three-dimensional (3D) electrical method is proposed. Combined with an urban exploration project in Hunan Province, China, the exploration efficiency and effect of the new mode of one-shaped layout arrangement exploration and conventional three-dimensional electric method exploration are compared and analyzed. The main process of this model is as follows: Firstly, determine the X and Y directions of electrophysical exploration according to the direction of the geological anomalies in the exploration area. Then, according to the exploration length and measuring point spacing in X and Y directions, the electrical grid parameters are determined. Finally, the coordinates of all power supply grids and the actual relative coordinates of the exploration area are calculated, and the power supply points are arranged in a pattern of one. The feasibility of the above model has been verified through the exploration project, and the results show that the exploration efficiency of this exploration model has been significantly improved compared with the conventional three-dimensional electric method, and the effect is excellent and highly applicable.The comparison of data shows that the number of power supplies and data acquisition of conventional 3D electrical method are 121 and 14520 respectively, while the number of new mode of one-shaped layout is only 17 and 2046 respectively, with a reduction of 85.9%. The research results can provide some reference for the exploration scheme design of urban karst groundwater channels.